Infective Aortic Valve Endocarditis Causing Embolic Consecutive ST-Elevation Myocardial Infarctions - Kanksha Peddi; Alexander L. Hsu; Tomas H. Ayala (Case Reports in Cardiology)
ST-elevation myocardial infarction (STEMI) is a rare and potentially fatal complication of infective endocarditis. We report the ninth case of embolic native aortic valve infective endocarditis causing STEMI and the first case to describe consecutive embolisms leading to infarctions of separate coronary territories. Through examination of this case in the context of the previous eight similar documented cases in the past, we find that infective endocarditis of the aortic valve can and frequently affect more than a single myocardial territory and can occur consecutively. Further, current treatment modalities for embolic infective endocarditis causing acute myocardial infarction are limited and unproven. This index case illustrates the potential severity of complications and the challenges in developing standardized management for such patients.